SISTEM INFORMASI MANAJEMEN INVENTORY STOK BARANG MENGGUNAKAN METODE FIRST-IN, FIRST-OUT (FIFO) DI PT SELECTA GRAGE JAYA CIREBON - Firdiansyah, Yuhanes; Novianti, Dian; Gunawan, Harry (INTI TALAFA, 2024)
The present information system has become a critical component or part of every human activity. This is not only for laypeople but also for companies and business applications, as well as for the hiring activities of each company. This suggests how information systems play an important part in the development of a company. The research conducted is one that concentrates on inventory data processing and computerized information presentation, which currently is inventory data processing which is currently streaming manually. A system that will be designed can/can solve problems that began from inventory data processing goods which are still undertaken by hand and processes that take a long time and lack efficiency in their operations. For that, it is particularly necessary to optimize the way information systems work through an information system design that is applied to web programming or JAVA and MySQL databases to solve problems or solutions of existing problems and be able to address corporate needs. The achievements of the stock management application include adding goods, inputting goods according to the goods that have been added according to the production date, and issuing goods release data according to the production date, WhatsApp rest API has been integrated as a notification to the supplier. The result of this design is expected to be a breakthrough for companies to thrive and thrive in their field.   Keyword: System, Information, Inventory, Metode FIFO